2013
DOI: 10.1589/jpts.25.1213
|View full text |Cite
|
Sign up to set email alerts
|

Association between Femoral Anteversion and Lower Extremity Posture upon Single-leg Landing: Implications for Anterior Cruciate Ligament Injury

Abstract: [Purpose] Increased femoral anteversion may occur with hip internal rotation and valgus knee alignment upon landing and is considered a risk factor for anterior cruciate ligament injury. We examined the relationship between femoral anteversion and joint motion and muscle activity of the lower extremity in terms of the risk factors for anterior cruciate ligament injury. [Subjects] Sixteen healthy females were divided on the basis of femoral anteversion into low and high groups. [Methods] Femoral anteversion was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Using one hand, the examiner palpated the greater trochanter until it was positioned laterally and maximally during passive internal rotation of the hip joint. The examiner then used a handheld goniometer with his other hand to measure the angle between the tibial lines, a line bisecting the medial and lateral malleoli, and an imaginary vertical line extending from the table 13 , 14 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Using one hand, the examiner palpated the greater trochanter until it was positioned laterally and maximally during passive internal rotation of the hip joint. The examiner then used a handheld goniometer with his other hand to measure the angle between the tibial lines, a line bisecting the medial and lateral malleoli, and an imaginary vertical line extending from the table 13 , 14 ) .…”
Section: Methodsmentioning
confidence: 99%
“…Previous authors have proposed an association between increased femoral antetorsion and a higher risk of noncontact ACL injuries, 2,3,19 possibly explained through an increase in the Q angle. Shultz et al suggested that greater hip antetorsion and associated intoeing could lead to excessive internal rotation of the tibia and greater rotatory stress on the knee.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in contrast with the findings of Kaneko and Sakuraba, who showed an association between increased femoral antetorsion and anterior tibial displacement during single-legged landing. 3 They postulated…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower extremity injuries related to changes in lower extremity alignment have been widely investigated in previous studies [4][5][6][7][8]. The relationships between such changes and injuries of this segment are clearly documented in the existing studies.…”
Section: Introductionmentioning
confidence: 99%